2005
DOI: 10.1200/jco.2005.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Soft Tissue Sarcoma or Malignant Mesenchymal Tumors in the First Year of Life: Experience of the International Society of Pediatric Oncology (SIOP) Malignant Mesenchymal Tumor Committee

Abstract: OS was satisfactory even when local treatment was not aggressive, although the prognosis was poor for infants with alveolar RMS or metastatic tumors. Chemotherapy toxicity was manageable with appropriate dose modification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0
11

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 23 publications
(25 reference statements)
0
68
0
11
Order By: Relevance
“…In a review of the Intergroup Rhabdomyosarcoma Study experience with infantile RMS, Orbach et al [17] found that genitourinary sites were more common among infants than among children and adolescents. However, these results were opposed by Salloum et al [10], who found that site distribution was equal in both age groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a review of the Intergroup Rhabdomyosarcoma Study experience with infantile RMS, Orbach et al [17] found that genitourinary sites were more common among infants than among children and adolescents. However, these results were opposed by Salloum et al [10], who found that site distribution was equal in both age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Orbach et al [17] reported botryoid histology as the most common histology and was more in infants than in older age group. While Salloum et al [10] reported that alveolar and poorly differentiated histologies were more common among infants.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel with their diminishing numbers and refinements in the identification of aggressive sarcomas that were previously included among the UNDS, the prognosis of the remaining UNDS has improved [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…As in older children, RMS in neonates is responsive to chemotherapy. Some NRSTS in neonates, however, are chemosensitive whereas others are not [ 159 ]. In view of the known long-term effects of radiotherapy, this should be used only as a treatment of last resort.…”
Section: Soft Tissue Sarcomasmentioning
confidence: 99%